Dilema Modernitas: Komodifikasi Seni Ketangkasan Domba dalam Pengembangan Pariwisata Berkelanjutan di Desa Rancabango, Garut - Ghaida Farisya; Ira Murwenie; Alam Avrianto (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study investigates the impact of the commodification of sheep agility arts on socio-cultural sustainability in Rancabango Village, Garut, in the context of sustainable tourism development. Its main objective is to analyze the challenges and opportunities in balancing the preservation of sheep agility arts with the demands of tourism. Using a critical social-humanities paradigm, this study focuses on the impact of cultural commodification on the village's economic growth and inequality, as well as changes in the identity and value of sheep agility art. This analysis is reinforced by MacCannell's theories of staged authenticity and cultural commodification, which provide a framework for understanding how local traditions are packaged for tourist consumption. This research uses qualitative methods with data collection techniques through Focus Group Discussions (FGD) involving key stakeholders such as the Village Head, BUMDes, artists, and community leaders. Participatory observation is used to gain a deeper understanding. The results show that commodification has transformed sheep agility art from a folk game into a structured cultural product with high economic value. Key findings include the positive impact on increasing village income, the impact on original cultural values, the emergence of economic inequality among practitioners, and the threat of land conversion that could damage the ecosystem that supports this art. This study concludes that there is a “modernity dilemma” that requires careful sustainable tourism management strategies so that economic development does not sacrifice the socio-cultural integrity of the community.